NEW OBSERVATIONS ABOUT LONTRA FELINA (MOLINA, 1782) IN THE COAST OF LIMA AND CALLAO, PERÚ - Pizarro, Jose (2023)
This note reports observations on the distribution Lontra felina (Molina, 1782) "marine otter" in eight new sites located in the district of Ventanilla, in the region of Callao, as well as in the districts of Santa Rosa, Ancón and Aucallama, in Lima, Perú. The fieldwork was carried out between January and June 2022 and six live animals and four freshly dead otters were observed. Both Bahía Blanca, in the district of Ventanilla, and the beaches of the Navy Club at Ancón, were the locations with more observations.